Dominance and state power in modern India: decline of a social order - Frankel, Francine R. (ed.); Rao, M.S.A. (ed.) (Delhi Oxford University Press, 1989)
In these two volumes, scholars of political science, sociology and history adopt a common set of concepts to analyse patterns of change in the ideological and structural foundations of dominance in India from the colonial period to the mid-1980s. Departing from modernization theories, these scholars set out an interactional framework of society-state relations where caste, class, ethnicity and dominance are treated as structures and processes, interacting with each other and with increasingly powerful state institutions. These comparative studies provide an explanation of how state policies undermine the religious legitimacy of the hierachical social order and, at the same time, facilitate the manipulation of linguistic, communal, caste and ethnic loyalties of diffuse class polarization. The analyses show that subordinate low caste-cum-class groups are mounting increasingly militant challenges to the hold of the upper castes and classes over state instituions which have provided the most important avenue of social mobility in modern India.
Keywords: Social classes